SUSTAINABLE VALUE CHAIN STRATEGY FOR TOFU SMEs - Issa Dyah Utami; Ika Deefi Anna; Nurul Hidayati (Jurnal Ilmiah Teknik Industri, 2022)
Globalization, free trade, and the current pandemic can be both a challenge and an opportunity for SMEs in Indonesia. One of the opportunities that arise from this phenomenon is the expansion of supply and demand networks. One of the SMEs in the food sector affected by the pandemic is the Tofu SME. Currently, only about 36% of tofu SMEs still survive in carrying out the production process. Most of the SMEs have problems in raw material inventory management, they do not yet have a standard warehouse. This problem minimizes their production capacity. Besides that, Tofu SMEs are still difficult to develop and sustain in the new normal era. For this reason, research on increasing the sustainability of SMEs needs to be carried out. The value chain analysis approach is used in the study to map the operational processes of SMEs and to identify activities and problems that make an important contribution to increasing the value of the SME business processes. K-means clustering method is used to group value chain levels. The Analytical Hierarchy Process (AHP) method is then used to choose a level-up strategy. Cluster 1 has the most members, which is 62 SMEs. Cluster 2 has the smallest member of 1 SME while cluster 3 has 9 SME members. The value coalition strategy is a recommended strategy to be applied to cluster 1 SME groups.